2019
DOI: 10.1039/c9ta00994a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the optical response of TiO2 and extending it into the visible region through surface activation with highly stable Cu5 clusters

Abstract: The photoabsorption of TiO2 in the UV gets enhanced and extended to the visible region by decoration with highly stable Cu5 clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 88 publications
6
70
0
1
Order By: Relevance
“…de Lara-Castells et al found that the Cu 5 cluster, when being deposited on the surface of TiO 2 , would donate an electron to Ti, favoring the formation of the active Ti 3+ species for CO 2 reduction. 22 , 27 A similar conclusion was also drawn by Seriani et al, who studied a system of TiO 2 deposited by Cu clusters (Cu x , x = 1–4). The authors also emphasized the importance of gap states created by the introduced Cu species, which could improve the optical response by reducing the band gap.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…de Lara-Castells et al found that the Cu 5 cluster, when being deposited on the surface of TiO 2 , would donate an electron to Ti, favoring the formation of the active Ti 3+ species for CO 2 reduction. 22 , 27 A similar conclusion was also drawn by Seriani et al, who studied a system of TiO 2 deposited by Cu clusters (Cu x , x = 1–4). The authors also emphasized the importance of gap states created by the introduced Cu species, which could improve the optical response by reducing the band gap.…”
Section: Introductionsupporting
confidence: 77%
“… 17 19 Therefore, a relatively low loading amount of Cu and supports with high specific surface area are often used, and a great effort was recently devoted to synthesize CuO x /TiO 2 with Cu in the morphologies of subnanoclusters or even a single atom. 20 − 22 After being introduced to TiO 2 , Cu species would bring about several benefits. The primary one is that the usable solar energy for photocatalysis could be extended to the visible light region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 , 42 Specifically, we employ a dispersion-corrected DFT-D3 ansatz , 43 , 44 given its excellent performance in describing the adsorption of subnanometer silver and copper clusters on oxide surfaces. 41 , 42 , 45 Structural optimizations and the calculation of interaction energies are carried out with the Perdew–Burke–Ernzerhof (PBE) density functional 46 and the Becke-Johnson (BJ) damping 43 for the D3 dispersion correction. Minor energy differences and the same trends were found when replacing the PBE functional by the PBEsol 47 , 48 counterpart in the DFT-D3 ansatz .…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we have selected the particular case of the Cu 5 cluster. This choice is motivated by a recent work 9 demonstrating via ab initio modeling and selected experiments that the deposition of a single monolayer of highly stable Cu 5 clusters onto a TiO 2 surface makes it an innovative visible-light photo-active material. Much more energy can be harvested from sunlight, and the coated titanium dioxide stores this energy temporarily in the form of charge pairs—electrons and holes—which is a perfect prerequisite for follow-up chemistry.…”
Section: Introductionmentioning
confidence: 99%